Human immunodeficiency virus integration protein expressed in Escherichia coli possesses selective DNA cleaving activity. - Sherman, P A (1990)
The human immunodeficiency virus (HIV) integration protein, a potential target for selective antiviral therapy, was expressed in Escherichia coli. The purified protein, free of detectable contaminating endonucleases, selectively cleaved double-stranded DNA oligonucleotides that mimic the U3 and the U5 termini of linear HIV DNA. Two nucleotides were removed from the 3' ends of both the U5 plus strand and the U3 minus strand; in both cases, cleavage was adjacent to a conserved CA dinucleotide. The reaction was metal-ion dependent, with a preference for Mn2+ over Mg2+. Reaction selectivity was further demonstrated by the lack of cleavage of an HIV U5 substrate on the complementary (minus) strand, an analogous substrate that mimics the U3 terminus of an avian retrovirus, and an HIV U5 substrate in which the conserved CA dinucleotide was replaced with a TA dinucleotide. Such an integration protein-mediated cleavage reaction is expected to occur as part of the integration event in the retroviral life cycle, in which a double-stranded DNA copy of the viral RNA genome is inserted into the host cell DNA.